Disaster recovery using VMware vSphere replication and vCenter site recovery manager : learn to bake in disaster recovery readiness for your vSphere Infrastructure using vCenter SRM 6.1 : leveraging array-based replication and vSphere Replication 6.1 /: learn to bake in disaster recovery readiness for your vSphere Infrastructure using vCenter SRM 6.1 : leveraging array-based replication and vSphere Replication 6.1. (2016) - GB, Abhilash
No abstract available